2012
DOI: 10.1002/stem.1199
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Heme Oxygenase‐1 in Neural Stem/Progenitor Cells as a Potential Mechanism to Evade Host Immune Response

Abstract: Besides their therapeutic benefit as cell source, neural stem/progenitor cells (NSPCs) exhibit immunosuppressive properties of great interest for modulating immune response in the central nervous system. To decipher the mechanisms of NSPC-mediated immunosuppression, activated T cells were exposed to NSPCs isolated from fetal rat brains. Analyses revealed that NSPCs inhibited T-cell proliferation and interferon-gamma production in a dosedependent manner. A higher proportion of helper T cells (CD4 1 T cells) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 61 publications
2
28
0
Order By: Relevance
“…Beyond the direct suppressive function of HO-1 (Chabannes et al, 2007), a recent study has identified a novel HO-1-driven mechanism of rat and human MSCs leading to the generation of IL-10 + Tr1 and TGF-β + Th3 Tregs in allo-and T-cell receptor-activated lymphocytes. Again, observations from in vitro co-cultures with T cells have implicated HO-1 in the anti-proliferative effects of rat NPCs (Bonnamain et al, 2012).…”
Section: Paracrine Signalingmentioning
confidence: 98%
See 1 more Smart Citation
“…Beyond the direct suppressive function of HO-1 (Chabannes et al, 2007), a recent study has identified a novel HO-1-driven mechanism of rat and human MSCs leading to the generation of IL-10 + Tr1 and TGF-β + Th3 Tregs in allo-and T-cell receptor-activated lymphocytes. Again, observations from in vitro co-cultures with T cells have implicated HO-1 in the anti-proliferative effects of rat NPCs (Bonnamain et al, 2012).…”
Section: Paracrine Signalingmentioning
confidence: 98%
“…Data in Table 1 are in part summarized in (Chamberlain et al, 2008;Hall et al, 2006;Martino and Pluchino 2006;Pluchino et al, 2009b;Rojewski et al, 2008;Uccelli et al, 2008;Yuan et al, 2011). (Cusimano et al, 2012;Jaderstad et al, 2010) aracrine IDO-kynurenine MSCs (h) T cells, DCs T cell apoptosis, inhibition of antigen presentation (Lanz et al, 2010;Matysiak et al, 2008Matysiak et al, , 2011Meisel et al, 2004;Plumas et al, 2005 Bonnamain et al, 2012;Chabannes et al, 2007;Moll et al, 2011) Paracrine VEGF NPCs Microglia/macrophages Inhibition of microglial activation, proliferation and phagocytosis (Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine LIF NPCs Th17 cells Inhibition of Th17 cell differentiation (Cao et al, 2011;Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine Galectins MSCs/NPCs T cells Inhibition of T cell proliferation (Gieseke et al, 2010;Sioud 2011;Yamane et al, 2010Yamane et al, , 2011 Endocrine/Paracrine TSG-6 MSCs Macrophages Inhibition of macrophage activation, proliferation and phagocytosis (Fisher-Shoval et al, 2012;Lee et al, 2009;Roddy et al, 2011) EVs miR transfer MSCs/NPCs Multiple Post-transcriptional regulation (Bruno et al, 2009;Chen et al, 2010;…”
mentioning
confidence: 99%
“…Within neural stem cell (NSC) populations, the presentation of MHC molecules is variable due to the isolation source and the inflammatory milieu, suggesting subpopulations of NSCs offer improved survival capacity [Bonnamain et al, 2012b]. These cells that survive, along with endogenous NSCs in the spinal cord, have the ability to modulate the local immune response, such as macrophage polarization and T cell phenotype after SCI, a characteristic shared with mesenchymal stem cells (MSCs) [Wang et al, 2009; Bonnamain et al, 2012a; English, 2013; Barbeau et al, 2014; Gao et al, 2014; Yan et al, 2014]. …”
Section: Stem Cell-mediatedmentioning
confidence: 99%
“…MSCs and NSCs modulate the immune cells through numerous mechanisms, including direct cell-cell contact and indirect contact via cytokines and signaling molecules [Wang et al, 2009; Bonnamain et al, 2012a; English, 2013; Luz-Crawford et al, 2013; Barbeau et al, 2014; Gao et al, 2014; Nazmi et al, 2014; Obermajer et al, 2014; Yan et al, 2014]. NSCs release soluble factors such as TGF-β1, prostaglandin E, nitric oxide, and hemeoxygenase-1 that increase regulatory T cell populations at the expense of effector T cells [Wang et al, 2009; Bonnamain et al, 2012a; Nazmi et al, 2014].…”
Section: Stem Cell-mediatedmentioning
confidence: 99%
“…TGF-β1 maintains immune tolerance, T-cell homeostasis and balances the immunogenicity of NSCs (20,55,56). In addition, HOs alone or in combination with NO production mediate immunosuppressive effects of NSCs (57,58), and growth factors and neurotrophins influence stem cell-immune cell interactions (54). Also im- mune-independent parameters, such as the ability to cope with oxidative stress, are critical for stem cell survival in vivo (59).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%